Native Tbilisians or Diaspora: Negotiating the Status of Armenians in Tbilisi - Ponomareva, Elli (ՀՀ ԳԱԱ Հնագիտության և ազգագրության ինստիտուտ)
According to contemporary ethnographic studies on the Armenians of Tbilisi local Armenians by and large perceive themselves as natives of Tbilisi rather than a diaspora community (Mkrtchian 2009: 305; Vardanyan 2006: 97). The data I collected in Tbilisi also confirms that perpetuation of the narrative on “Armenian Tiflis” constitutes an important element of Armenian identity for a majority of research participants. Ժամանակակից ազգագրական հետազոտությունները ցույց են տալիս, որ թիֆլիսահայերը հիմնականում իրենց ընկալում են որպես բնիկ թիֆլիսցի, այլ ոչ թե Սփյուռքի մի մաս (Mkrtchian 2009: 305; Vardanyan 2006: 97)։ Դաշտային աշխատանքի միջոցով Թբիլիսիում հավաքած մեր տվյալները նույնպես հաստատում են, որ «հայկական Թիֆլիսի» մասին նարատիվի անընդհատ կրկնելը ինֆորմանտների մեծամասնության համար կազմում է հայկական ինքնության կարևոր մի տարր։ Согласно современным антропологическим исследованиям, тифлисские армяне в основном воспринимают себя коренными тифлиссцами, нежели частью армянской диаспоры. Но во время моих полевых исследований 2015-2016г. проявилась еще одна тенденцияих самовосприятия и самовыражения - тифлисские армяне как часть диаспоры.
Keywords: History